Estágio curricular supervisionado: percepções do enfermeiro supervisor, do docente orientador e do gestor - Ramos, Tierle Kosloski (2019)
Considering the complexity that encompasses the general education of nurses, based on the quality of teaching, this process is evidenced as a responsibility of educational institutions with society. This way, throughout the training, in addition to theoretical-practical contents, the National Curricular Guidelines point out the obligation to carry out the Supervised Curricular Internship. Its development reflects actions resulting from partnerships between the educational institution and the health services, the management organization of the service, the provision of health professionals for the reception of the student and his/her commitment to the training. Considering the importance of this stage in the training of the nurse professional, as well as the necessity and importance of their continuous evaluation, the objective was to analyze the process of accomplishment of the Supervised Curricular Internship from the perspective of internship supervisors, instructors and managers in the training of nurses. Specific objectives included: knowing the profile of study participants; to analyze the influences of the Supervised Curricular Internship in health services; to analyze the weaknesses and potentialities of the Supervised Curricular Internship from the perspective of internship supervisors, instructors and managers. The present study deals with qualitative, exploratory-descriptive field research. The study was carried out in a nursing undergraduate course at a Federal University of Rio Grande do Sul. Nine internships instructor professors, seven nurses supervising hospital care, six nurses supervising primary care and four managers participated in the study, totaling 26 participants. Data collection took place between February and July 2018, through a semi-structured interview. The ethical principles described in Resolution 466/2012 of the National Health Council were respected. Data analysis was performed through the Bardin Content Analysis. The definition of this stage and the singularities that permeate its development emerged as a result of the perspective of those involved in the Supervised Curricular Internship. Potentialities of the internship and its influence on nurses’ training were also described, including the possibility of self-knowledge and self-reflection of the student, the deepening of knowledge and the development of autonomy. Among the limitations, it was highlighted the lack of physical structure and human resources. The study could identify and correlate the attributions and limitations of the student, the internships instructor professors, the nurse supervisor and the manager in the development of the internship. It was also possible to analyze the possibilities, limitations and influences of the internship before the interaction between teaching and the service, identifying the need for advances in its effectiveness, as well as the range of benefits that this relationship can result both for the educational institution, as well as for health services. Regarding the evaluation, it was possible to understand the current panorama, as well as the limitations and suggestions for improvement from the perspective of those involved, including the evaluation instrument used. In view of the diversity of general limitations regarding the internship, it was possible to raise suggestions for (re) thinking and (re) structuring improvement points, making it possible to advance nurses’ training.